Study of Converting waste to energy: Iraq’s potential and the role of artificial intelligence in sustainable solutions - Ghada S.mohammed; Wala’a A.Mahdi; Riyam M.Alsammarraie (Journal of Madenat Alelem University College, 2024)
Energy supply and waste management are becoming increasingly important for Iraq and the Middle East. Population growth, rapid urbanization, and economic development have increased waste generation. In addition, when energy demand exceeds supply, it leads to frequent power outages. Waste-to-energy is a new approach that offers environmental, economic, and security benefits by integrating waste treatment with clean energy production. This paper examines several waste-to-energy methods in Iraq today, including gasification, incineration, and others. These technologies have the potential to reduce global greenhouse gas emissions, increase local and sustainable energy sources, and reduce the amount of garbage that ends up in landfills. Strategies for waste-to-energy are also discussed, as are the challenges facing waste-to-energy programs in Iraq. The role of the world and the Middle East in waste-to-energy, especially electricity, is also discussed. In addition, future prospects for Iraq are highlighted, including strengthening government initiatives, the possibility of international cooperation, and utilizing large amounts of waste as a resource for energy generation. Several suggestions have been made to improve the method waste-to-energy projects are implemented in Iraq. These suggestions include developing a strong infrastructure for waste management and energy conversion, using appropriate and advanced waste-to-energy technologies, such as electricity. Also, efficient policies and regulations should be enacted to support waste-to-energy. Iraq can also seize the opportunity to develop strategic partnerships with international companies specialized in environmental technology and waste-to-energy and also focus on marketing and awareness to enhance community awareness of the benefits of waste-to-energy and electricity generation, which would encourage increased investment projects in this field.